THE SIMULATION AND DATA ANALYSIS OF TEMPERATURE SENSOR - Hilal Fauzi Ramadhan; Retno Dwi Kartika Sari; Adnan Prasetyo Alamsyah; Adrian Fadhillah; Rizki Nurhikmah; Sarah Aribah Miftahulfallah; Widya Rahma; Ari Firia; Dea Amelia Saputri; Irmansyah Irmansyah; Irzaman Irzaman (Program Studi Fisika Universitas Negeri Jakarta, 2021)
The study have successfully simulated 40 units data of temperature sensor during heating process and cooling process. Simulated data in temperature sensor has interval time 3 to 18 seconds for 5 iterations that are combined with other 7 data temperature sensor until get 40 data iterations. The data which has been simulated and then plotted into a graph with the x-axis is time and y-axis is average heating process or cooling process. The graph formmed cupped-down with quadratic function for heating process and cupped-up for cooling process.